IDE Support of String-Embedded Languages - S. Grigorev; E. Verbitskaia; M. Polubelova; A. Ivanov; E. Mavchun (Моделирование и анализ информационных систем)
Complex information systems are often implemented by using more than one programming language. Sometimes this variety takes a form of one host and one or few string-embedded languages. Textual representation of clauses in a string-embedded language is built at run time by a host program and then analyzed, compiled or interpreted by a dedicated runtime component (database, web browser etc.) Most general-purpose programming languages may play the role of the host; one of the most evident examples of the string-embedded language is the dynamic SQL which was specified in ISO SQL standard and is supported by the majority of DBMS. Standard IDE functionality such as code completion or syntax highlighting can really helps the developers who use this technique. There are several tools providing this functionality, but they all process only one concrete string-embedded language and cannot be easily extended for supporting another language. We present a platform which allows to easily create tools for string-embedded language processing.